2022
DOI: 10.1515/lingvan-2020-0109
|View full text |Cite
|
Sign up to set email alerts
|

Surprise questions in spoken French

Abstract: This paper offers a pragmatic account of two wh-questions in French used non-canonically - c’est quoi, ce N and qu’est-ce que constructions. It is claimed that in this non-canonical use, both constructions express surprise. As these constructions may be syntactically ambiguous between an information-seeking reading and a surprise reading, it is expected that the two readings differ in terms of prosody. This hypothesis is supported by the results of a production experiment. Experimental evidence shows significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…For a prosodic analysis of French wh-questions that are ambiguous between an information-seeking and a non-canonical meaning of surprise (or expectation denial), see alsoBrunetti et al (2021), as well asCelle and Pélissier (2021).…”
mentioning
confidence: 99%
“…For a prosodic analysis of French wh-questions that are ambiguous between an information-seeking and a non-canonical meaning of surprise (or expectation denial), see alsoBrunetti et al (2021), as well asCelle and Pélissier (2021).…”
mentioning
confidence: 99%
“…The study compared the prosody of string-identical SQs and ISQs that were elicited by means of context descriptions. The design of the experiment as well as the types of interrogatives were inspired by Celle & Pélissier (2021). All data, analysis code, and research materials of the study are available at the Open Science Framework repository: https://osf.io/knygh/.…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, the only study that directly addresses the prosody of syntactically unmarked interrogative sentences expressing surprise is Celle & Pélissier's (2021) study on French that revealed significant prosodic differences between syntactically similar ISQs and SQs: SQs exhibited lengthening, slower speech rate, and less frequent final rising contours (but no difference in mean pitch or pitch range). The lengthening observed in French SQs could also be associated with signalling emotional expressivity.…”
Section: Introductionmentioning
confidence: 99%
“…Pour le français, le terme « question de surprise » a été d'abord utilisé surtout pour les questions en qu'est-ce que et en quoi dans les articles d'Agnès Celle avec ses co-auteurs (Celle et al 2021, Celle et Pélissier 2022, dont voici un exemple (1) avec un qu'est-ce que non-argumental :…”
Section: Introductionunclassified